Smartphone‐Based Training of Cognitive Bias Modification: Efficacy for Reducing Social Anxiety in Chinese Adolescents. - Mao, Ningning; Li, Ting; Li, Chieh; Ding, Ruifeng; Zhang, Qin; Cui, Lixia (Journal of Child & Family Studies, 2023)
Social anxiety is an increasing mental health concern for adolescents in the international community, including China, where access to psychotherapy is still limited. Training in cognitive bias modification of interpretation (CBM-I) for ambiguous social situations has demonstrated efficacy in improving social anxiety. Smartphone-based CBM-I has the potential to be an accessible tool to help address the mental health needs of adolescents. However, no prior studies have explored smartphone-based CBM-I targeting social anxiety in adolescents. We examined the effect of an eight-session smartphone-based training of cognitive bias modification of interpretation (CBM-I) on the social anxiety of Chinese adolescents. Twenty-eight participants who scored in the top ten percent of Social Anxiety Scale (SAS-A) and the Brief Fear of Negative Evaluation (BFNE) were randomly assigned to the training group and the waitlist group. Both groups completed pre- and post-tests of interpretation bias and social anxiety. Participants in the training group logged into the smartphone-based CBM-I application twice a week for four weeks to receive the intervention. The waitlist group received the same pre-and post-tests only during the 4-week waiting time. Results revealed that the CBM-I training group significantly increased positive interpretation bias and decreased negative interpretation bias, social anxiety, and fear of negative evaluation. The waitlist group did not have any significant changes in the above measures. The eight-session smartphone-based CBM-I intervention showed the expected intervention effect for Chinese adolescents coping with social anxiety, demonstrating its potential as an effective tool for reducing social anxiety for the population. Highlights: Developed an 8-session smartphone-based training of CBM-I for social anxiety reduction. Developed culturally and developmentally adapted CBM-I training materials for Chinese adolescents. Found a significant reduction in social anxiety and fear of negative evaluation in the CBM-I training group.